Replacement of Astaxanthin With Lutein in Diets of Juvenile Litopenaeus vannamei: Effects on Growth Performance, Antioxidant Capacity, and Immune Response - Fang, HaoHang; He, XuanShu; Zeng, HuLong; Liu, YongJian; Tian, LiXia; Niu, Jin (Frontiers in Marine Science, 2021)
An 8-week feeding experiment was conducted to investigate whether diet supplementation of lutein could result in similar growth performance, antioxidant capacity, and immunity of Litopenaeus vannamei when compared to dietary astaxanthin. Juvenile L. vannamei (initial body weight: 0.64 ± 0.04 g) were fed with one of five isonitrogen and isolipids diets with/without lutein or astaxanthin [control group (C); the lutein (L) groups contained 0, 62.5, 75, 87.5 ppm lutein, respectively, the astaxanthin (A) group contained 50 ppm astaxanthin]. Results showed that dietary supplementation of lutein ranging from 62.5 to 75 ppm resulted in similar growth performance (WGR, SGR, FCR, and SR) of L. vannamei compared with the A group (P > 0.05). Apart from that, no statistical difference was observed in antioxidant parameters (hemolymph T-AOC, hemolymph MDA, and RNA expression level of GSH-PX, CAT), anti-inflammatory ability (Relish, Rho, and HSP70) and apoptosis-related gene expression (Caspase3) among lutein treatments ranging from 62.5 to 87.5 ppm and the A group (P > 0.05). These results indicate that a dose of 62.5–75 ppm of lutein was suitable in the diet of L. vannamei for substituting dietary astaxanthin.